2006
DOI: 10.1074/jbc.m603952200
|View full text |Cite
|
Sign up to set email alerts
|

Oxidant-induced Activation of Type I Protein Kinase A Is Mediated by RI Subunit Interprotein Disulfide Bond Formation

Abstract: Here we demonstrate that type I protein kinase A is redoxactive, forming an interprotein disulfide bond between its two regulatory RI subunits in response to cellular hydrogen peroxide. This oxidative disulfide formation causes a subcellular translocation and activation of the kinase, resulting in phosphorylation of established substrate proteins. The translocation is mediated at least in part by the oxidized form of the kinase having an enhanced affinity for ␣-myosin heavy chain, which serves as a protein kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
199
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 227 publications
(211 citation statements)
references
References 28 publications
8
199
4
Order By: Relevance
“…1a). Consistent with our past studies 12,13 , we found that H 2 O 2 -or VEGF-induced oxidant formation oxidized PKARIa to a disulphide state (Fig. 1a).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…1a). Consistent with our past studies 12,13 , we found that H 2 O 2 -or VEGF-induced oxidant formation oxidized PKARIa to a disulphide state (Fig. 1a).…”
Section: Resultssupporting
confidence: 92%
“…In this study, we identified PKA as a target of oxidation that can transduce VEGF-dependent oxidant formation into pro-angiogenic signalling. The treatment of BAECs or isolated aortic vessels with VEGF resulted in disulphide dimerization of PKARI associated with its activation 12 . Once activated, oxidized PKA stimulated ERK, a principle mediator of growth factor signalling that couples with upregulation of genes involved in endothelial cell migration and proliferation 21 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1B). RIα was shown previously to be targeted only in response to certain stimuli such as capping with an antigen (19) or generation of reactive oxygen species (20). The selective targeting of RIβ seen only when one enriches for mitochondria suggests that RIβ may have a unique role in regulating mitochondrial structure and/or function.…”
Section: Resultsmentioning
confidence: 99%